Incidence of Postoperative Stroke after Coronary Artery Bypass Surgery and its Risk Factors - SM Mir Mohammad Sadeghi (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: One of the most important and fatal complications of the coronary artery bypass surgery is postoperative stroke. The aim of this study was to determine the incidence of postoperative stroke after coronary artery bypass surgery and its risk factors.METHODS: This retrospective study was performed on the documents of 1386 patients undergoing first coronary artery bypass surgery during 2004 to 2008 in Sina hospital in Isfahan, Iran. Variables such as gender, age, number of days hospitalized in intensive care after surgery, type of surgery, duration of staying under heart and lung machine, history of hypertension, PCI, chest pain, diabetes and ejection fraction were assessed. FINDINGS: Among all subjects 1033 were male and 353 were female. Incidence of stroke after surgery was 1.4 percent. Univariate tests showed history of diabetes (p=0.018), ejection fraction levels (p=0.001) and duration of hospitalization in intensive care unit (p=0.01, CIMD=4.8- 6.6) had significant relationship with stroke. Simultaneous analysis showed the level of ejection fraction (p =0.005, CIOR=1.646–17.382, OR average to good=5.348, p=0.01, CIOR=1.535–24.875, OR weak to good=6.18) and length of stay in intensive care unit (p=0.001, CIOR=1.136 – 1.34, OR=1.234) had significant relationship.CONCLUSION: According to the results of this study, ejection fraction and length of stay in intensive care unit are risk factors of postoperative stroke.